Diagnostic Sensitivity of Unenhanced CT for Cerebral Venous Thrombosis: Can Clot Density Measurement Replace CT Venogram? - Snehansh Roy Chaudhary; Mohamed Chunara; Chris McLeavy; Haisum Qayyum; James Cusack; David Paton; James Hare; Akash Ganguly (Indian Journal of Radiology and Imaging, 2023)
Objectives Cerebral venous sinus thrombosis is an important cause of stroke in young adults. Noncontrast-enhanced CT head (NECT) is almost always the first investigation. Our objectives were as follows: 1. How accurately does venous sinus density on NECT predict the presence of clot on CT venogram (CTV)? 2. Whether repeated measurements changed the confidence? 3. How many venous sinus thrombus would be missed if we do not do a CTV? 4. Can clot density measurement replace CTV? Methods Multicenter case–control study was designed with data from seven hospitals. Inclusion criteria: all CT and magnetic resonance imaging venograms with a prior NECT, performed between 1.1.2018 and 31.12.2018 (12 months), were included. Hounsfield unit (HU) values were calculated at the site of highest density on the NECT. Logistic regression analysis was performed using STATA. Result Two-hundred seventy-seven cases met the criteria with 33 positive cerebral venous thrombosis (density on NECT 60–92 HU) and 244 negative examinations (density on NECT 31–68 HU). Area under the curve for average clot density on NECT was 0.9984. Conclusion We found a strong relationship between sinus density on NECT and outcome of CTV. Repeating density measurements did not add any predictive value or changed outcome. Advances in Knowledge Density 70 HU or higher on NECT always resulted in a positive CTV but would miss a fifth of the positives. Cutoff at 60 HU would not miss any but result in significant false positives. An efficient option could be to limit CTV to sinus densities 60 to 70 HU only. However, a larger study would be required for such change in practice.